Normative Standards Of Vo2Max As A Measuring Tool For Athlete Selection In Badminton And Futsal Sports In Bojonegoro District - Surya Aprilia; Wahyu Setia Kuscahyaning Putri; Benny Widya Priadana; Romadhiyana Kisno Saputri (Journal of Sports Medicine and Physiotherapy, 2025)
Background: Physical condition is a term that describes the degree of fitness and health of a person's body, which includes various components such as strength, agility, durability, speed, power, balance, flexibility, and reaction. One of the primary indicators for measuring aerobic endurance capacity is VO2Max. A high VO2Max level is essential in sports that require high intensity and prolonged gameplay, such as badminton and futsal. Bojonegoro district has significant athletic potential, but there are no established normative VO2Max standards that can be used as a reference in the systematic selection and development of athletes. Objectives: This study aims to develop normative VO2Max standards as a benchmark for athlete selection in two sports, namely badminton and futsal, in Bojonegoro Regency. VO2Max is a key indicator of aerobic capacity and cardiovascular system efficiency, which is very important in supporting athlete endurance and performance. Methods: This study employed a quantitative approach using the Bleep Test instrument to measure VO2Max in 73 active athletes affiliated with sports clubs in Bojonegoro. Results: The study results showed that the average VO2Max for badminton athletes was 28.0 and for futsal athletes was 41.4, with standard deviations of 5.7 and 4.3, respectively. Based on category classification, most badminton athletes fell into the moderate category, while futsal athletes ranged from moderate to high categories. Conclusion: These differences reflect the physiological characteristics required in each sport, with futsal demanding higher aerobic endurance due to its higher intensity and longer match duration. This study produced VO2Max category norms for each sport, which can be used as a reference in the athlete selection process and in the development of targeted training programmes.